Descartes's Meditations an introduction - Wilson, Catherine 1951- (Cambridge introductions to key philosophical texts, 2003)
In this introduction to a classic philosophical text, Catherine Wilson examines the arguments of Descartes' famous Meditations, the book which launched modern philosophy. Drawing on the reinterpretations of Descartes' thought of the past twenty-five years, she shows how Descartes constructs a theory of the mind, the body, nature, and God from a premise of radical uncertainty. She discusses in detail the historical context of Descartes' writings and their relationship to early modern science, and at the same time she introduces concepts and problems that define the philosophical enterprise as it is understood today. Following closely the text of the Meditations and meant to be read alongside them, this survey is accessible to readers with no previous background in philosophy. It is well-suited to university-level courses on Descartes, but can also be read with profit by students in other disciplines